2020
DOI: 10.3390/genes11070720
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Transcriptome Analysis Reveals Nr4a1 Mediated Glucose Metabolism Dysregulation in Response to High-Fat Diet

Abstract: Obesity is associated with an increased risk of developing cardiovascular disease (CVD), with limited alterations in cardiac genomic characteristics known. Cardiac transcriptome analysis was conducted to profile gene signatures in high-fat diet (HFD)-induced obese mice. A total of 184 differentially expressed genes (DEGs) were identified between groups. Based on the gene ontology (GO) term enrichment and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis of DEGs, the critical role of cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Despite the established role of obesity in cardiovascular disease, there are limited data regarding the transcriptional effects of obesity on the heart. In a similar mouse model, existing literature has shown that obesity-induced transcriptional changes in the left ventricle largely affect genes and pathways involved in cardiac metabolism, including glycolysis as well as remodeling ( 52 ). Here we present the effects of obesity on atrial gene expression, which in particular include genes involved in cardiac metabolism, cell-cell connectivity, cardiac remodeling, and cytokine signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the established role of obesity in cardiovascular disease, there are limited data regarding the transcriptional effects of obesity on the heart. In a similar mouse model, existing literature has shown that obesity-induced transcriptional changes in the left ventricle largely affect genes and pathways involved in cardiac metabolism, including glycolysis as well as remodeling ( 52 ). Here we present the effects of obesity on atrial gene expression, which in particular include genes involved in cardiac metabolism, cell-cell connectivity, cardiac remodeling, and cytokine signaling.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent multi-omics analysis revealed that cardiac lipid metabolism was changed in type-2 diabetic db/db mice which was supported by metabolomics and transcriptomics ( 55 ). In mice fed, an obesogenic diet global gene expression analysis revealed obesity related changes in glucose metabolism pathways ( 56 ). In line with such transcriptomic data, the proteomic results presented here confirm that obese phenotype propagates cardiac lipid utilization whilst simultaneously reducing glucose metabolism homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…NR4A1, regulated glycolysis and glucose transport in liver, muscle, and adipose tissue through different signaling pathway [ 18 20 ]. The expression of NR4A1 was downregulated in diabetic, ob/ob, and db/db mice.…”
Section: Discussionmentioning
confidence: 99%